The influence of intranasal peste des petits ruminants vaccine application methods on the induction of immune responses in goats: clinicopathological and immunohistochemical findings - Ezeasor, Chukwunonso Kenechukwu; Shoyinka, Shodeinde Vincent; Emikpe, Benjamin Obukowho; Udeani, Theophilus Kachidelu; Nwankpra, Nick; Bodjo, Charles Sanne; Sabri, Mohd Yusoff (Chulalongkorn University, 2021)
Intranasal administration of peste des petits ruminants (PPR) vaccine may induce mucosal and systemic immune responses in goats but little is known about the influence of the vaccine application methods. This study reports the influence of two different intranasal vaccine application methods on the immune responses in goats following intranasal PPR vaccination. Twenty, male west African dwarf goats were divided into 4 groups (n=5). Groups A and B were vaccinated intranasally (IN) with live attenuated PPR vaccine (Nigeria 75/1) by either nasal dropper (Group A) or nasal spray (Group B) methods and compared with the subcutaneous route of vaccination (Group C) and unvaccinated goats (Group D) for 28 days. PPR blocking ELISA based on the H-antigen demonstrated high-titres of PPRV-specific antibodies in all vaccinated goats with peak percentage inhibitions of 79.3% (day 14); 69.8% (day 21) and 86.6% (day 21) for IN-Drop; IN-Spray and Subcutaneous vaccination groups, respectively. Histomorphological assessment of the lungs showed the development of bronchus-associated lymphoid tissues (BALT) in Group B (IN-Spray). Immunohistochemistry showed PPR viral antigens in the lymphoid cells of the BALT in Group B and in the spleen and mediastinal lymph nodes of all the vaccinated goats after 28 days of vaccination. This study shows that the choice of application methods for intranasal PPR vaccine delivery may affect the induction of PPR-specific systemic immune responses. IN Drop method may result in an earlier peak in the antibody titer but the IN-Spray method holds greater potential for pulmonary protection against PPR induced pulmonary disease.